Relaxation kinetics of the Na+/glucose cotransporter. - Loo, D D (1993)
An important class of integral membrane proteins, cotransporters, couple solute transport to electrochemical potential gradients; e.g., the Na+/glucose cotransporter uses the Na+ electrochemical potential gradient to accumulate sugar in cells. So far, kinetic analysis of cotransporters has mostly been limited to steady-state parameters. In this study, we have examined pre-steady-state kinetics of Na+/glucose cotransport. The cloned human transporter (hSGLT1) was expressed in Xenopus oocytes, and voltage-clamp techniques were used to monitor current transients after step changes in membrane potential. Transients exhibited a voltage-dependent time constant (tau) ranging between 2 and 10 ms. The charge movement Q was fitted to a Boltzmann relation with maximal charge Qmax of approximately 20 nC, apparent valence z of 1, and potential V0.5 of -39 mV for 50% Qmax. Lowering external Na+ from 100 to 10 mM reduced Qmax 40%, shifted V0.5 from -39 to -70 mV, had no effect on z, and reduced the voltage dependence of tau. Qmax was independent of, but tau was dependent on, temperature (a 10 degrees C increase increased tau by a factor of approximately 2.5 at -50 mV). Addition of sugar or phlorizin reduced Qmax. Analyses of hSGLT1 pre-steady-state kinetics indicate that transfer upon a step of membrane potential in the absence of sugar is due to two steps in the reaction cycle: Na+ binding/dissociation (30%) and reorientation of the protein in the membrane field (70%). The rate-limiting step appears to be Na+ binding/dissociation. Qmax provides a measure of transporter density (approximately 10(4)/microns 2). Charge transfer measurements give insight into the partial reactions of the Na+/glucose cotransporter, and, combined with genetic engineering of the protein, provide a powerful tool for studying transport mechanisms.